From instinct to evidence: the role of data in country decision-making in Chile - Ximena Paz Aguilera; Consuelo Espinosa-Marty; Carla Castillo-Laborde; Claudia Gonzalez (Taylor & Francis Group, 2017)
Background: The Chilean health system has undergone profound reforms since 1990, while going through political upheaval and facing demographic, health, and economic transformations. The full information requirements to develop an evidence-informed process implied the best possible use of the available data, as well as efforts to improve information systems. Objective: To examine, from a historical perspective, the use of evidence during the health sector reforms undertaken in Chile from 1990 to date, and to identify the factors that have both determined improvements in the data and facilitated their use. Methods: A qualitative methodological approach was followed to review the Chilean experience with data on decision-making. We use as the primary source our first-hand experience as officials of the Ministry of Health (MOH) and the Ministry of Finance before and during the reform period considered. A literature review was also conducted, using documents from official sources, historical accounts, books, policy reports, and articles published in indexed journals reviewing and discussing the reform process, looking for the use of data. Results: The Chilean health-care reform process was intensive in its use and production of information. The MOH conducted several studies on the burden of disease, efficacy of interventions, cost-effectiveness, out-of-pocket payments, fiscal impact, social preferences, and other factors. Policy and prioritization frameworks developed by international agencies strongly influenced the use of data and the study's agenda. Conclusions: The Chilean example provides evidence that tradition, receptiveness to foreign ideas, and benchmarking with international data determined the use of data, facilitated by the political influence of physicians and, later, other technocrats. Internationally comparable statistics are also shown to play a significant role in the policy debate.